2004
DOI: 10.3171/jns.2004.100.1.0088
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, migration, and differentiation of human neural stem/progenitor cells after transplantation into a rat model of traumatic brain injury

Abstract: This study shows that expandable human neural stem/progenitor cells survive transplantation, and migrate, differentiate, and proliferate in the injured brain. These cells could potentially be developed for transplantation therapy in cases of traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 50 publications
5
82
0
2
Order By: Relevance
“…Modo et al (11) obtained similar results with conditionally immortalized mouse neuroepithelial cells transplanted into the striatum of the ischemic brain. None of our cells expressed the oligodendrocyte marker NG2 at this time point; this finding is consistent with the results of Wennersten et al (36), who transplanted human neural progenitors into a rat model of cortical trauma. However, we (N.U., unpublished data) and others (37) have shown that hCNS-derived neurospheres or other neural progenitors can become oligodendrocytes that myelinate axons of the myelin-deficient shiverer mouse.…”
Section: Discussionsupporting
confidence: 82%
“…Modo et al (11) obtained similar results with conditionally immortalized mouse neuroepithelial cells transplanted into the striatum of the ischemic brain. None of our cells expressed the oligodendrocyte marker NG2 at this time point; this finding is consistent with the results of Wennersten et al (36), who transplanted human neural progenitors into a rat model of cortical trauma. However, we (N.U., unpublished data) and others (37) have shown that hCNS-derived neurospheres or other neural progenitors can become oligodendrocytes that myelinate axons of the myelin-deficient shiverer mouse.…”
Section: Discussionsupporting
confidence: 82%
“…Cryopreservation of NPCs has not been studied in detail, except as a part of transplantation studies [6,[21][22][23]. The present study demonstrates that deep-freezing (-70°C) may allow banking of murine neurospheres, with preserved functionality yielding a minimum of 50% NPC recovery.…”
Section: Discussionmentioning
confidence: 94%
“…16 Since the Suicide gene therapy using neural stem cells S Li et al discovery and characterization of neural stem/progenitor cells, many studies have been performed on neuronal restoration by transplantation after ischemic and traumatic injuries of the central nervous system. 8 It has been shown that neural stem/progenitor cells migrate to the regions where neurogenesis is required such as ischemic and traumatic lesions. Aboody et al 6 have also demonstrated the exceptional migratory ability of NSCs to brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we isolated neural stem cells (NSCs) from Sprague-Dawley rat embryos and expanded them using neural stem cell expansion kit/Neurosphere system (R&D Systems) and tested the use of NSCs, which recently have been shown to possess the ability to proliferate, migrate and then differentiate along the neuronal and glial lines, [6][7][8] as TK-expressing cells.…”
mentioning
confidence: 99%